Prognostic Factors Impacting Surgical Outcomes in Patients With Cervical Spondylotic Myelopathy. Issue 10 (21st December 2022) - Su, Brian W.; Tadepalli, Vaib; Kamalapathy, Pramod N.; Shimer, Adam
Abstract : The purpose of surgical decompression in patients who have CSM is to stop the progression of symptoms and hopefully improve function. It is critical to understand prognostic factors that affect the outcome. Factors intrinsic to the patient that can adversely affect outcomes include diabetes, older age, tobacco use, the presence of mental health disease, and obesity. MRI imaging findings of T2 hyperintensity and clinical duration and severity of symptoms is also associated with poorer outcomes. Patients should be counseled regarding the efficacy of decompressive procedures for CSM and given realistic expectations based on their unique biophysical profiles.